1997
DOI: 10.2307/30141509
|View full text |Cite
|
Sign up to set email alerts
|

Noncompliance with Universal Precautions and the Associated Risk of Mucocutaneous Blood Exposure among Danish Physicians

Abstract: Compliance with Universal Precautions is unacceptably low, as reflected by the circumstances of MCE. Increased efforts to ensure education in Universal Precautions, easy accessibility of protective barriers, and improved design of the barriers are necessary to improve compliance and reduce the risk of MCE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…Other reasons include perceived reduction in dexterity when wearing gloves, and the absence of penalties [36]. This study also reported lack of penalty even for not using protective devises.…”
Section: Discussionsupporting
confidence: 50%
“…Other reasons include perceived reduction in dexterity when wearing gloves, and the absence of penalties [36]. This study also reported lack of penalty even for not using protective devises.…”
Section: Discussionsupporting
confidence: 50%
“…In the works of Nelsing in Danemark, glove was worn by 63 health workers i.e. 23.4% (Nelsing et al, 1997). This difference could be explained by the negligence or the nonperception of the risk given the weak prevalence of HIV and the availability of prophylactic treatments in those countries.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Failure to use protective devices while performing invasive procedures occurs for various reasons, including inconvenience, unavailability of the devices, interference with work, and the belief that compliance is not protective. 35 Injury reductions from engineered sharps injury protective devices have varied according to the thoroughness of implementation training, perceptions of risk of percutaneous injury and blood-borne infection, and level of training and motivation to use the devices. 36 Cost analyses indicate that protective devices are likely to be cost-effective long term.…”
Section: Lessons Regarding Percutaneous Injuries Amongmentioning
confidence: 99%